The determinants of pregnancy health literacy among youth in Bogalay Township, Ayeyarwaddy Region, Myanmar - Lat, Tun W.; Lynn, May P.; Mya, Kyaw S. (International Journal Of Community Medicine And Public Health, 2022)
Background: Focusing on adolescent reproductive health is very important, as 16% of the world's population is adolescents. This study aimed to identify the determinants of teenage pregnancy health literacy among youth and explore the perception of teenage pregnancy among youth and their guardians. Methods: We conducted a cross-sectional study with a mixed-method approach to identify the determinants and perception of pregnancy health literacy among youth in Bogale Township, Ayeyarwaddy region, Myanmar, between July and December 2020. We did the face-to-face personal interviews with guided self-administered questionnaires among 310 youth and individual depth interviews with 12 youth and 12 of their parents. Results: About 43% (95% CI 37.1%, 48.1%) were well-versed in pregnancy health literacy issues. This study discovered that youth with high school education and less had a 6.8 (95% CI =1.4, 34.7) fold increase in odds of having poor pregnancy health literacy compared to those with higher education. Moreover, youth who could not earn their income was approximately 5.7 times more likely to have poor pregnancy health literacy than those who could earn. The majority of youth requested to disseminate reproductive health information through various media and channels and that health facilities be well-equipped to provide reproductive health care services to teenagers. Most parents believed that sexual and reproductive health education should be begun only when school=age children reach puberty. Conclusions: The all-inclusive schooling system should be strengthened continuously in basic schools and universities. Sexual and reproductive health education/teaching programs and adolescents-friendly reproductive health services should be effectively implemented to prevent teenage pregnancy and ensure safer sex practices among teenagers. School-based sexual education programs must involve and assist parents and teachers in taking a more active role in SRH education in schools. In addition, young people should be well-equipped and have secured better and more employment opportunities.